Prediction of Pressure and Temperature in CO2 Injection Wells Based on Analytical Modeling. - Tchouka Singhe, Arron A. (Schriftenreihe des Energie-Forschungszentrums Niedersachsen (EFZN), 2013)
Kurzfassung ; ACKNOWLEDGEMENTS ; DEDICATION ; Table of Contents ; LIST OF FIGURES ; LIST OF TABLES ; NOMENCLATURE ; 1. INTRODUCTION ; 2. LITERATURE REVIEW ; 3. PREDICTION OF THERMODYNAMIC AND TRANSPORT PROPERTIES ; 4. INJECTION WELLBORE FLOW EQUATIONS ; 5. APPLICATION OF THE MODELS TO WELLBORE INJECTION ; 6. THE SIMULATION CODES AND THE GRAPHICAL USER INTERFACE ; 7. VALIDATION OF THE MODELS AND THE PROCEDURE ; 8. CONCLUSIONS AND RECOMMENDATIONS ; 9. REFERENCES ; APPENDIX A- Further Calculations ; APPENDIX B - Thermodynamic and Transport Properties in the Tables.